GREEN ALGAE Ulva sp. AS RAW MATERIAL FOR BIOGAS PRODUCTION - Tri Dian Oktiana; Joko Santoso; Mujizat Kawaroe (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Ulva sp. is a non edible seaweed and posses a high growth rate. Therefore, this species is potential to be developed as a raw material for biogas production. One important factor on the biogas production is to determine organic loading rate (OLR). The aim of this study was to determine the potential of Ulva sp. as a raw material for biogas and to find out the optimum loading rate in the process of biogas production.  Biogas production was carried out in the digester with a capacity of 22 l that was made of fiber and equipped with a manual stirrer and gas flow meter to measure gas production. Parameters analised were pH, COD, TSS, VSS, and gas composition. Organic loading rates used in this study were 0.5, 1, 1.5, and 2 kg COD.m-3.day-1.  The results showed that the optimum loading rate was 1.5 kg COD.m-3.day-1. In the loading rate of 1.5 kg COD.m-3.day-1, we obtained the highest biogas production rate of 12.14 l/day with methane content of 42.96%, average COD removal of 51.97%, and methane production of 0.33 l/g COD.   Keywords: anaerobic, biogas, COD, loading, methane, Ulva sp.